Two Novel Polysaccharides From Clitocybe squamulosa: Their Isolation, Structures, and Bioactivities - Guo, Dongdong; Lei, Jiayu; Xu, Lijing; Cheng, Yanfen; Feng, Cuiping; Meng, Junlong; Chang, Mingchang; Geng, Xueran (Frontiers in Nutrition, 2022)
Abstract: The crude polysaccharides from the fruiting bodies of Clitocybe squamulose (CSFP) were isolated by hot water extraction. And two novel polysaccharides CSFP1-β and CSFP2-α were further purified by DEAE- 52 anion exchange and Sephacryl S-400 gel filtration chromatography, and the purities were reached to 98.44% and 97.83%, respectively. The structural characteristics and bioactivities of CSFP, CSFP1-β and CSFP2-α were identified by the combination of chemical and instrumental analysis. Results showed that CSFP was clustered by spherical substances in a honeycomb shape, CSFP1-β and CSFP2-α were interwoven by reticular and fibrous structures, respectively. Purified components CSFP1-β and CSFP2-α both had the characteristics of typical infrared absorption peaks of polysaccharides, and contents of nucleic acid and protein decreased significantly. Simultaneously, CSFP was composed mainly of glucose, mannose, galactose and rhamnose, the molecular weight was 1.948×104 Da. CSFP1-β was composed mainly of glucose, galactose and mannose, CSFP2-α was composed of glucose, both of their molecular weight distribution was uneven. Meanwhile, compared with CSFP, the antioxidant activities of CSFP1-β and CSFP2-α were significantly improved (p < 0.05). And both of them showed good abilities to bind free cholesterol and bile acid salt in vitro, the binding abilities of which were 68.62%, 64.43% and 46.66 mg/g and 45.05 mg/g, respectively. All CSFP, CSFP1-β and CSFP2-α had good bacteriostatic effects and which showing a linear concentration increasing relationship. In addition, CSFP exhibited obvious promoting effect on growth of RAW264.7 cells and has potential immunomodulatory, anti-inflammatory and anti-tumor activities.